PENGARUH PRODUK DAN BRAND COMMUNITY TERHADAP LOYALITAS MEREK PADA KOMUNITAS MOTOR NMAX DI KOTA BENGKULU - Almunawar, M. Ikhsan; Wahyudi, Dedy (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
The research was conducted at the NMAX Motorcycle Community in Bengkulu, with the formulation of the problem: Do Products and Brand Communty have an effect on brand loyalty at the NMAX Motorcycle Community in Bengkulu, Questionnaire data collection tools, Documentation and interviews as well as research analysis tools using SPSS 2.60. Based on the results of the research The effect of product and brand community on brand loyalty in the NMAX motorbike community in Bengkulu can be concluded as follows: Product has a significant effect on brand loyalty in the NMAX motorbike community in Bengkulu Brand community has a significant effect on brand loyalty in the NMAX motorbike community in Bengkulu. Product (X_1) and Brand Community (X_2) together have a significant effect on Brand Loyalty (Y) in the NMAX Motor Community in Bengkulu. (X_1) and Brand Community (X_2) contributed an influence of 0.732 or 74% to Brand Loyalty (Y) in the NMAX Motorcycle Community in Bengkulu while the remaining 0.268 or 26% was influenced by other variables not included in this study. Keywords: Product, Brand Community and Brand Loyalty